Analisis Ketrampilan Gerak Badminton dengan Media Pembelajaran Virtual Reality (VR) pada Mahasiswa - Alexander, Bimo; Kustiawan, Andri Arif; Zulham (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze the effect of Virtual Reality (VR) learning media on Badminton motor skills in university students. Virtual Reality (VR) is considered a motor learning innovation that can simulate immersive game situations, thereby improving the quality of visual stimuli, kinesthetics, and motor decisions. The study design used a quasi-experimental pretest-posttest model on 30 students participating in the Badminton Student Activity Unit at the University. The assessment instrument included serve, forehand, backhand, and smash tests. The results showed a significant increase in the average motor skill score between before and after the VR intervention, with an average increase of 22.4%. Statistical analysis showed a p value <0.05, which means that VR media is effective in improving Badminton motor skills. These findings indicate that VR is feasible to be implemented as a technology-based motor learning innovation in universities. This study contributes to the development of physical education technology and offers an alternative approach in Badminton learning.